Soldier dog - Angus, Sam (Square Fish, 2014)
It is 1914, and the world is on the brink of its first World War. Thirteen-year-old Stanley watches as his brother leaves for combat, leaving him with an angry father for family. All Stanley has are his family's greyhound puppies, but one day Stanley wakes up to find both his father and the dogs gone. With nowhere else to go, Stanely lies his way into the army, and is given the task of training a greyhound named Bones in the army's War Dog School.